Gut Microbiota: The Missing Link Between Helicobacter pylori Infection and Metabolic Disorders? - Martin-Nuñez, Gracia M.; Cornejo-Pareja, Isabel; Clemente-Postigo, Mercedes; Tinahones, Francisco J. (Frontiers in Endocrinology, 2021)
Helicobacter pylori (H. pylori) is a gram-negative bacterium that infects approximately 4.4 billion individuals worldwide. Although the majority of infected individuals remain asymptomatic, this bacterium colonizes the gastric mucosa causing the development of various clinical conditions as peptic ulcers, chronic gastritis and gastric adenocarcinomas and mucosa-associated lymphoid tissue lymphomas, but complications are not limited to gastric ones. Extradigestive pathologies, including metabolic disturbances such as diabetes, obesity and nonalcoholic fatty liver disease, have also been associated with H. pylori infection. However, the underlying mechanisms connecting H. pylori with extragastric metabolic diseases needs to be clarified. Notably, the latest studies on the topic have confirmed that H. pylori infection modulates gut microbiota in humans. Damage in the gut bacterial community (dysbiosis) has been widely related to metabolic dysregulation by affecting adiposity, host energy balance, carbohydrate metabolism, and hormonal modulation, among others. Taking into account that Type 2 diabetic patients are more prone to be H. pylori positive, gut microbiota emerges as putative key factor responsible for this interaction. In this regard, the therapy of choice for H. pylori eradication, based on proton pump inhibitor combined with two or more antibiotics, also alters gut microbiota composition, but consequences on metabolic health of the patients has been scarcely explored. Recent studies from our group showed that, despite decreasing gut bacterial diversity, conventional H. pylori eradication therapy is related to positive changes in glucose and lipid profiles. The mechanistic insights explaining these effects should also be addressed in future research. This review will deal with the role of gut microbiota as the linking factor between H. pylori infection and metabolic diseases, and discussed the impact that gut bacterial modulation by H. pylori eradication treatment can also have in host’s metabolism. For this purpose, new evidence from the latest human studies published in more recent years will be analyzed.